“Mental maps”: Between memorial transcription and symbolic projection - Guelton, Bernard (Frontiers in Psychology, 2023)
“The mental map” is a concept that has been used and defined in numerous ways. The cognitive map, and the concept map–also known as the “heuristic” or “mind” map–are the two distinct contextual meanings covered by the term mental map in the present article. In the mental map domain, the first major field of study is geography, spatial cognition, and neurophysiology and it aims to understand how the route taken by a subject (or a set of subjects) in space leads to memorization and internal representation(s). In general, the externalization of these representations takes the form of drawings, positioning in a graph, or oral/textual narratives, but it is primarily reflected as a behavior in space that can be recorded as tracking items. A second field of study, one which is geared more toward exploratory and combinatorial uses, is the concept (also heuristic or mind) map which consists in organizing notions, concepts, and information in the form of tree graphs or graphs that can be used to produce diagrams and flowcharts. The aim is projective, for clarification and discovery purposes or for data organization and visualization. To date, very few studies in the literature have examined the similar, overlapping and oppositional features in what is broadly referred to as “representation(s) of space” and “space(s) of representation.” How can we better apprehend the complex notion of “mental map?” The question of memorial transcription? Of “symbolic projection?” Can we identify meeting points between these two polarities and, if possible, a continuum? Through the notion of cognitive graph, recent advances in the understanding of brain mechanisms enable us to approach the distinctions between cognitive map and conceptual map as an articulated and continuous whole.